Structural and Functional Characterization of the Type Three Secretion System (T3SS) Needle of Pseudomonas aeruginosa - Lombardi, Charlotte; Tolchard, James; Bouillot, Stephanie; Signor, Luca; Gebus, Caroline; Liebl, David; Fenel, Daphna; Teulon, Jean-Marie; Brock, Juliane; Habenstein, Birgit; Pellequer, Jean-Luc; Faudry, Eric; et al. (Frontiers in Microbiology, 2019)
The Type Three Secretion System (T3SS) is a macromolecular protein nano-syringe used by different bacterial pathogens to inject effectors into host cells. The extracellular part of the syringe is a needle-like filament formed by the polymerization of a 9-kDa protein whose structure and proper localization on the bacterial surface is are a key determinants for efficient toxin injection. Here, we combined in vivo, in vitro, and in silico approaches to characterize the Pseudomonas aeruginosa T3SS needle and its major component PscF. Using a combination of mutagenesis, phenotypic analyses, immunofluorescence, proteolysis, mass spectrometry (MS), atomic force microscopy (AFM), electron microscopy (EM) and molecular modeling, we propose a model of the P. aeruginosa needle which that exposes the N-terminal region of each PscF monomer towards the outside of the filament, while the core of the fiber is formed by the C terminal helix. Among mutations introduced into the needle protein PscF, D76A and P47A/Q54A caused a defect in the assembly of the needle on the bacterial surface, although the double mutant was still able to killcytotoxic on macrophages in T3SS-dependent a manner in an attenuated dependent manner and formed filamentous structures in vitro. These results suggest that the T3SS needle of P. aeruginosa adopts a common T3SS needles displays an architecture that is similar to that of other bacterial species needles studied to date and highlight the fact that small, targeted perturbations in the needle assembly can inhibit T3SS function. Therefore, the T3SS needle represents an excellent drug target represents a very interesting target for small molecules acting as virulence blockers development that could disrupt pathogenesis of affect a broad range of pathogenic bacteria.